2015
DOI: 10.1016/j.bbrc.2015.01.112
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-induced CXCL8 expression counteracts its actions by inducing tumor neovascularization

Abstract: a b s t r a c tPatients with pancreatic ductal adenocarcinoma (PDAC) are frequently complicated with metastatic disease or locally advanced tumors, and consequently need chemotherapy. Gemcitabine is commonly used for PDAC treatment, but with limited efficacy. The capacity of gemcitabine to generate reactive oxygen species (ROS) in human pancreatic cancer cells, prompted us to examine its effects on the expression of pro-inflammatory cytokines and chemokines. We observed that gemcitabine enhanced selectively th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…We previously unraveled the involvement of ROS generation in gemcitabine-induced CXCL8 expression [20]. Likewise, NAC, an inhibitor of ROS, significantly reduced gemcitabine-induced increases in SA-β-gal-positive cell numbers, suggesting that gemcitabine induced cell senescence partly through gemcitabine-induced ROS generation, as previously observed [27].…”
Section: Discussionsupporting
confidence: 72%
See 4 more Smart Citations
“…We previously unraveled the involvement of ROS generation in gemcitabine-induced CXCL8 expression [20]. Likewise, NAC, an inhibitor of ROS, significantly reduced gemcitabine-induced increases in SA-β-gal-positive cell numbers, suggesting that gemcitabine induced cell senescence partly through gemcitabine-induced ROS generation, as previously observed [27].…”
Section: Discussionsupporting
confidence: 72%
“…We previously observed that gemcitabine treatment enhanced intra-tumoral CXCL8 expression and that anti-CXCL8 antibody administration reduced tumor formation when it was given with the combination of gemcitabine [20]. On the contrary, anti-CXCL8 antibody failed to reduce gemcitabine-induced increases in SA β-gal-positive cell numbers ( Figure 3C).…”
Section: Gemcitabine-induced Cell Senescence In Human Pancreatic Cancmentioning
confidence: 71%
See 3 more Smart Citations